Determinan Gangguan Muskuloskeletal pada Petani Tembakau di Kelurahan Antirogo Kabupaten Jember - Sabila, Selma Naf’an; Fatmawati, Heni; Marchianti, Ancah Caesarina Novi (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2023)
One of the most common occupational diseases in the world is musculoskeletal disorders. Tobacco farmers have ahigher risk of musculoskeletal disorders in the form of lower back pain than other farmers because transdermalexposure to nicotine to tobacco farmers has an impact on intervertebral disc nutrition and increased levels of proinflammatory cytokines. The purpose of this study was to analyze the determinants of musculoskeletal disorders intobacco farmers in Antirogo Village, Jember Regency, which is known as the largest tobacco producing district inEast Java. This research is an analytic observational study with a cross-sectional study design. The number of samplesis 53 people based on the Slovin formula with the consecutive sampling method. Musculoskeletal disorders weremeasured using the Nordic Body Map. Data analysis used was descriptive univariate analysis and bivariate analysisusing the Spearman test, Chi-Square 2x3, and Kolmogorov-Smirnov. Significant variables were re-analyzed bymultivariate through ordinal logistic regression analysis. The results showed that most of the tobacco farmers inAntirogo Village, Jember Regency experienced musculoskeletal disorders with moderate complaints (45.3%) mostlyin the waist (33.9%), upper neck (32%), and back (30.1%). Bivariate analysis showed that the significant variableswere age (p= 0.000), years of work (p= 0.000), and work position (p= 0.008). When followed by multivariate analysisit appears that the only significant variable was years of work (p = 0.003). It can be concluded from this study thatthe determinant of musculoskeletal disorders in tobacco farmers in Antirogo Village, Jember Regency is years ofwork.